Kinetic Study on Pyrolysis of Oil Palm Frond - Soon, V.; Chin, Bridgid; Lim, A. (2016)
The pyrolysis of oil palm frond is studied using thermogravimetric analysis (TGA) equipment. The present study investigates the thermal degradation behaviour and determination of the kinetic parameters such as the activation energy (EA ) and pre-exponential factor (A) values of oil palm frond under pyrolysis condition. The kinetic data is produced based on first order rate of reaction. In this study, the experiments are conducted at different heating rates of 10, 20, 30, 40 and 50 K/min in the temperature range of 323-1173 K under non-isothermal condition. Argon gas is used as an inert gas to remove any entrapment of gases in the TGA equipment.